2022
DOI: 10.5009/gnl210474
|View full text |Cite
|
Sign up to set email alerts
|

Changing Patterns of Causative Pathogens over Time and Efficacy of Empirical Antibiotic Therapies in Acute Cholangitis with Bacteremia

Abstract: Background/Aims To select appropriate empirical antibiotics, updates on the changes in pathogens are essential. We aimed to investigate the changes in pathogens and their antibiotic susceptibility in acute cholangitis (AC) with bacteremia over a period of 15 years. Furthermore, the efficacy of empirical antibiotic therapies and the risk factors predicting antibiotic-resistant pathogens (ARPs) were analyzed. Methods A total of 568 patients with AC and bacteremia who were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
1
0
0
Order By: Relevance
“…was the most commonly reported in patients with stent occlusion (65%) when compared with the other group (P=0.027). In agreement with this study, a study on 568 patients with acute cholangitis reported that the most common pathogen was Klebsiella (10) . Additionally, a study reported that Klebsiella spp.…”
Section: Discussionsupporting
confidence: 90%
“…was the most commonly reported in patients with stent occlusion (65%) when compared with the other group (P=0.027). In agreement with this study, a study on 568 patients with acute cholangitis reported that the most common pathogen was Klebsiella (10) . Additionally, a study reported that Klebsiella spp.…”
Section: Discussionsupporting
confidence: 90%